Effect of various phase change materials (paraffin wax/hydrogenated vegetable oil) packed in a fabricated shell and tube type heat exchanger. (2021) - Manikandan, R.; Shabir, Mohd F.; Raja, T.; Chandra, P. Muniraja; Salman, Syed; Vasim Akram, I.
Abstract: Researchers are often trying to find out the various renewable energy sources to continuously feed the growing energy demands as well as storing the generated energy with appropriate known technology. In line of the above, in order to store the energy, phase changing material (PCM) playing the major role. The phase changing materials exhibit better efficiency due to its energy storage capacity, and keep supplies constant thermal energy when need arises. Normally the characteristics of the phase change materials are charging, storing and following this, final step is discharging the heat to the selected medium through the phase changing materials and the same could be used for many applications starts from domestic to industrial spectrum. In this present study, the paraffin wax and hydrogenated vegetable oil have been used as the phase changing materials. To experimentally analyze the coefficient of thermal expansion of the phase changing material, the tube and shell type heat exchanger have been used. Similarly the efficiencies of the thermal energy storage (TES) capacity of the subjected material have been verified, with the intention of employ the same system for the applications like cold storage plant, refrigeration, domestic heating and automobile sectors.